2015
DOI: 10.1001/jamadermatol.2014.4777
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Next Melanoma in Patients With Familial and Sporadic Melanoma by Number of Previous Melanomas

Abstract: We found a stable 2- to 3-times elevated risk by number of previous melanomas for patients with either familial or sporadic melanoma. Notable risk in young patients with familial melanoma during first 5-year follow-up after first melanoma may suggest that it is important to refer these patients for clinical genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 24 publications
2
25
1
1
Order By: Relevance
“…The increasing number of patients diagnosed with invasive cutaneous malignant melanoma (CMM) that develop one or more additional CMMs, i.e., multiple primary invasive cutaneous malignant melanomas (MPMs), may be correlated to increasing incidence of CMM and improved survival over the last decades . The expected life time risk of an additional CMM varies between 1.3 and 8.6% . Several clinical and tumor‐related characteristics are associated with MPMs, e.g., older age, male gender, personal, or family history of CMM .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing number of patients diagnosed with invasive cutaneous malignant melanoma (CMM) that develop one or more additional CMMs, i.e., multiple primary invasive cutaneous malignant melanomas (MPMs), may be correlated to increasing incidence of CMM and improved survival over the last decades . The expected life time risk of an additional CMM varies between 1.3 and 8.6% . Several clinical and tumor‐related characteristics are associated with MPMs, e.g., older age, male gender, personal, or family history of CMM .…”
mentioning
confidence: 99%
“…The expected life time risk of an additional CMM varies between 1.3 and 8.6% . Several clinical and tumor‐related characteristics are associated with MPMs, e.g., older age, male gender, personal, or family history of CMM . Decreasing tumor thickness in subsequent CMMs has been reported .…”
mentioning
confidence: 99%
“…Thus, Sweden has a high proportion of patients diagnosed with a single primary melanoma at risk of developing multiple primary melanomas. There are a few previous studies investigating different aspects of multiple primary melanomas in Sweden, but none has focused on Western Sweden (12)(13)(14)(15). Over the past 20 years this geographical region has shown a higher incidence of melanoma than the national average, and is therefore an important area for melanoma research (16).…”
mentioning
confidence: 99%
“…Family history of melanoma should signal vigilance for clinical follow-up. 21,22 Our recent study showed that a family history of cancer X is a risk factor of second cancer X in melanoma patients. 7 Common SPCs with increased familial risks in melanoma patients included prostate, breast, colorectal and squamous cell skin cancers, for which screening methods would be available.…”
Section: Discussionmentioning
confidence: 99%